Ecosystems, food, agriculture, and ethics - Rolston, Holmes, 1932-2025, author; Springer Science and Business Media, publisher (Colorado State University. Libraries, 2014)
Humans live in towns and are civilized, but by nature too are residents on landscapes, rural. An ecology lies in the background of culture, providing ecosystem services. Some dimensions of health pervade both wild and agricultural nature. Humans in recent times have dramatically transformed and degraded landscapes, a huge ecological footprint. Humans now are entering an Anthropocene Epoch, escalating industrial agriculture, in both developed and developing nations, hoping for and threatening global sustainable development. A wiser goal might be a sustainable biosphere, the ultimate unit of survival.
Keywords: agriculture; farming; landscapes; ecology; ecosystem services; industrial agriculture; developing nations; sustainable development; sustainable biosphere; Anthropocene Epoch